Substrate oxidation does not influence middle distance running performance: a randomized controlled crossover trial - Buga, A.; Buxton, J. D.; Plank, E.; Minor, J. D.; Sterrett, M. T.; Brooks, C. A.; Niemann, T. R.; Troxel, M. P.; Bryarly, A.; Furry, Z.; Hannon, C.; Muench, J.; et al. (Nutrients, 2025)
Objective: Recent work has challenged the notion that preferred substrate oxidation is a key determinant of exercise performance. This investigation tested middle-distance running performance, in the fed state, to control for glycogen and exercise-induced hypoglycemia (EIH) confounders.